2010
DOI: 10.1109/tcomm.2010.080310.100026
|View full text |Cite
|
Sign up to set email alerts
|

Weakly-Constrained Codes for Suppression of Patterning Effects in Digital Communications

Abstract: ???This material is presented to ensure timely dissemination of scholarly and technical work. Copyright and all rights therein are retained by authors or by other copyright holders. All persons copying this information are expected to adhere to the terms and constraints invoked by each author's copyright. In most cases, these works may not be reposted without the explicit permission of the copyright holder." ???Copyright IEEE. Personal use of this material is permitted. However, permission to reprint/republish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 15 publications
(34 reference statements)
0
17
0
Order By: Relevance
“…The overall results indicate that single ring MRR with rather high power coupling coefficient from bent to straight waveguide can provide reasonable amplitude fluctuation reduction when cascaded up to five devices. To improve the proposed technique weakly-constrained codes for suppression of patterning effects could be added [26]. The considerable improvement has been shown previously with active device after the converter [21] for clock recovery.…”
Section: Resultsmentioning
confidence: 97%
“…The overall results indicate that single ring MRR with rather high power coupling coefficient from bent to straight waveguide can provide reasonable amplitude fluctuation reduction when cascaded up to five devices. To improve the proposed technique weakly-constrained codes for suppression of patterning effects could be added [26]. The considerable improvement has been shown previously with active device after the converter [21] for clock recovery.…”
Section: Resultsmentioning
confidence: 97%
“…Numerical simulations of a 15.6 Gbs CO-OFDM system with 100 subcarriers and 7-channel WDM have shown that up to 1dB improvement in the system Q-factor can be obtained when this power allocation method is applied. We believe that the proposed power pre-emphasis technique can be also successfully combined with the constrained channel coding [25,26] to suppress other detrimental nonlinear and linear impairments such as patterning effects due to inter carrier interference.…”
Section: Resultsmentioning
confidence: 99%
“…As shown above, the error statistics for 1400 km was uneven. In general, the type of error statistics can allow (or cannot allow) to reduce the bit-error rate using the special encoding schemes developed for that purpose ( [10,9]). So, it is useful to estimate the degree of "unevenness" of the statistics for the different transmission distances and for different signal powers.…”
Section: Error Statistics Behaviourmentioning
confidence: 99%
“…In particular, they manifest themselves as uneven error statistics (i.e. patterning effects), as they make the bit-error rate (BER) dependent on the data being transmitted through the fiber ([4]- [10]). The statistical knowledge of error distributions can be used to improve the error correction schemes ([6]- [10]).…”
Section: Introductionmentioning
confidence: 99%